PENERAPAN 7 KEBIASAAN ANAK INDONESIA HEBAT DALAM MEMBENTUK SIKAP DISIPLIN SISWA KELAS 2 - Aninda Ayu Salsabilah; Nurul Febrianti; Abdul Halim; Lisna Hikmawaty (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The formation of disciplinary character in elementary school students is an important aspect in supporting the success of the learning process and children’s behavioral development. This study aims to describe the implementation of the 7 Habits of Great Indonesian Children program in shaping the disciplinary attitudes of second-grade students at SDN Pejuang VII. This research employed a descriptive qualitative approach focusing on students’ understanding and activities in applying these habits both at school and at home. The research subjects consisted of four second-grade students and one homeroom teacher. Data were collected through observation, interviews, and documentation, and then analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the 7 Habits of Great Indonesian Children had a positive impact on students’ discipline formation, including increased compliance with school rules, punctuality, cleanliness habits, and responsibility in completing assignments. The role of teachers and parental support were also important factors in the successful implementation of these habits. Therefore, the 7 Habits of Great Indonesian Children program can serve as an effective strategy for developing disciplinary character among elementary school students sustainably in daily life. ABSTRAK Pembentukan karakter disiplin pada siswa sekolah dasar merupakan salah satu aspek penting dalam mendukung keberhasilan proses pembelajaran dan perkembangan perilaku anak. Penelitian ini bertujuan untuk mendeskripsikan penerapan program 7 Kebiasaan Anak Indonesia Hebat dalam membentuk sikap disiplin siswa kelas II di SDN Pejuang VII. Penelitian menggunakan pendekatan kualitatif deskriptif dengan fokus pada pemahaman serta aktivitas siswa dalam menerapkan kebiasaan tersebut di lingkungan sekolah maupun di rumah. Subjek penelitian terdiri atas 4 siswa kelas II dan 1 wali kelas. Data dikumpulkan melalui teknik observasi, wawancara, dan dokumentasi, kemudian dianalisis menggunakan tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penerapan 7 Kebiasaan Anak Indonesia Hebat memberikan dampak positif terhadap pembentukan disiplin siswa, seperti meningkatnya kepatuhan terhadap aturan sekolah, kebiasaan datang tepat waktu, menjaga kebersihan, serta tanggung jawab dalam menyelesaikan tugas. Peran guru dan dukungan orang tua juga menjadi faktor penting dalam keberhasilan penerapan kebiasaan tersebut. Dengan demikian, program 7 Kebiasaan Anak Indonesia Hebat dapat menjadi salah satu strategi pembentukan karakter disiplin siswa sekolah dasar secara berkelanjutan dalam kehidupan sehari-hari.